Analisis Dampak Kegiatan Pembangunan Putaran-U di Jalan Maulana Hasanudin, Kecamatan Batu Ceper, Kota Tangerang terhadap Aspek Geografi Sosial - Aditya, Muhammad Fajar; Anwar, Syafri (Lembaga Yasin AlSys, 2025)
The construction of a U-turn facility on Maulana Hasanudin Street, Batu Ceper District, Tangerang City, is a strategic infrastructure initiative aimed at enhancing regional connectivity and accessibility. This study seeks to analyze the impact of the development on the community’s social geography, educational accessibility, and traffic density in the study area. A descriptive mix methods approach was employed, combining qualitative analysis with line density techniques to assess traffic congestion levels. The findings reveal that the U-turn development has generated complex effects. In terms of social geography, it altered travel patterns, influencing social interactions while simultaneously strengthening local community solidarity. Economically, the project stimulated activity in sectors catering to construction workers' needs, although other sectors faced adaptation challenges. Educational accessibility exhibited disparities in travel time between morning and afternoon, highlighting the need for traffic policies that are responsive to school activity rhythms. Traffic analysis indicated that, while the U-turn effectively managed vehicle flow during regular hours, congestion persisted during peak times (17:00–18:00 WIB) and weekends, with a traffic imbalance showing 30% higher density from Benda toward Maulana Hasanudin. These findings underscore the necessity for ongoing evaluation of both the social and technical impacts of urban infrastructure development.